(untitled) (Revista de Estudos da Linguagem, 2006)
The Portuguese syllabic system contains a consonantal onset withtwo elements C2. The first one corresponds to an obstruent, plosiveor fricative, and the second to a tap or a lateral. This paper presentsan interesting configuration of the linguistic variational processrelated to the fishermen located in Florianópolis, S.C., Brazil. Themultilinear phonology exposes the phenomenon under theuniversal principles and the local parameters, recovering an unifiedand satisfactory description. A scientific explanation of thephonological system, theme of this article, asks for an evaluationof the research and a revision in the educational area, includingthe Applied Linguistics.